2019
DOI: 10.3390/polym11030466
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Fabrication of Chitin/Poly(butylene succinate)/Chondroitin Sulfate Nanoparticles Ternary Composite Hydrogel Scaffold for Skin Tissue Engineering. Polymers, 2014, 6, 2974–2984

Abstract: The authors wish to make a change to the published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…It has been reported that an enhancement of 3D morphology results in improved mechanical strength and water retention so that a matrix can easily take up nutrients for the establishment of cell adhesion and differentiation. 35,36 AFM Analysis. The surface morphology of the wheat grassreinforced collagen aerogels validates the presence of well-oriented interconnections.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an enhancement of 3D morphology results in improved mechanical strength and water retention so that a matrix can easily take up nutrients for the establishment of cell adhesion and differentiation. 35,36 AFM Analysis. The surface morphology of the wheat grassreinforced collagen aerogels validates the presence of well-oriented interconnections.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In brief, the samples were immersed in distilled water and incubated at room temperature for different time periods. At certain intervals (1,3,5,7,22,24,36, and 48 h), aerogels were removed from water and the wet weight was measured. The swelling behavior of the aerogels was calculated using the following equation (eq 1)…”
Section: ■ Experimental Sectionmentioning
confidence: 99%